Katakan Tidak Pada Bullying: Ceria Bersama Mewarnai Dunia Kecil Mereka - Gustiawan, Deni; Risnawati, Henny; Santosa, Bambang; Sari, Hastuti Indra; Zulmita, Zulmita; Rahmadiana, Rahmadiana; Kasusilaningrum, Tyas; Fikri, Fikri (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2025)
This activity was carried out by lecturers and HIMMA (Management Student Association) from the Swadaya Business and Communication Institute (SWINS) at Rumah Yatim Duren Sawit, East Jakarta, with the theme "Say No to Bullying: Cheerful Together Coloring Their Little World". Rumah Yatim Duren Sawit fosters 100 orphans, both boys and girls, aged between 7-17 years. The purpose of this activity is to provide joy to the foster children so that they can live their childhood lives with joy. The method used is a counseling method regarding the dangers of bullying and preventive measures against bullying behavior through video screenings, as well as providing drawing and coloring training, while inviting the foster children of Rumah Yatim Duren Sawit to play an active role in participating in various interactive & educational games. The result of this community service activity is the realization of a child's life that is free from bullying, and faces childhood life with full motivation and joy.